Pension Scheme Governance in the UK: A Qualitative Study - Ross-Jones, Thomas (2006)
Pension scheme governance is an area that has not historically attracted much attention from companies and academia alike. However, the importance of pension scheme governance has recently been realised and many companies are now trying to manage the risks that are inherent in their occupational pension schemes. Consequently, academic interest in the subject has also begun to increase and this paper will look at this burgeoning field of pension scheme governance. However, this paper has a radically different approach to the subject than the previous, more quantitative, research in that it will follow a qualitative research methodology of semi-structured interviews followed by an Interpretive Phenomenological Analysis of these interviews, which has previously not been undertaken. The aim of this research was to identify and understand the different experiences of pension scheme governance that exist in the pensions industry. Different experiences of pension scheme governance were found to exist in the pensions industry and these differences largely related to whether the research participant had experience of large or small pension schemes. What this research indicates is that there are many variances in the operation of pension scheme governance in practice with most of the best practices occurring with larger pension schemes, due to the impracticalities of these taking place on smaller pension schemes. Thus, this research suggests other governance mechanisms that could well be utilised by smaller pension schemes to improve their standards of governance. These mechanisms include: governance audits; codes of practice; and professional independent trustees. This research also indicates that it may well be useful for a review comparable to that conducted by Derek Higgs, on non-executive directors in public companies, to be conducted on the role and effectiveness of independent professional trustees in ensuring the good governance of pension schemes.